Long-Term Performance of the Water Infiltration and Stability of Fill Side Slope against Wetting in Expressways - Yuedong Wu; Xiangyu Zhou; Jian Liu (Applied Sciences, 2022)
Different settlements and instabilities of unsaturated subgrade subjected to wetting have been paid increasing attention in the southeast coastal areas of China. However, the treatments are costly when they are used in engineering. In addition, the long-term performances of the treatments are unclear. Based on seepage theory for unsaturated soils, a novel subgrade using a capillary barrier was proposed in this study to reduce the different settlements and stabilities. Compared with previous studies, a capillary barrier was merely applied in the landfill. The long-term performance and feasibility of a capillary barrier applied in a tilted subgrade slope is worthy of study, particularly in humid climates. Using Geo-Studio, the feasibility was verified by comparing a conventional subgrade with a subgrade using a capillary barrier in southeast coastal areas in terms of pore-water pressure, water content, settlement, and the safety factor. The numerical results showed that the subgrade using a capillary barrier could provide significant improvements in the performance of reducing the impact of pore-water pressure distribution it suffered from, so as to lead to smaller different settlements. The vertical settlement of the pavement using a capillary barrier over a 1 year period was 1 cm. Compared with a conventional subgrade, the settlement fell by 94%, and the safely factor increased by 15% for the subgrade using the capillary barrier.